1996
DOI: 10.1007/bf00196648
|View full text |Cite
|
Sign up to set email alerts
|

The pathway for systemic electrical signal conduction in the wounded tomato plant

Abstract: Abstract. The pathway of a systemic electrical signal possibly linking wounding and the systemic synthesis of proteinase inhibitor was investigated in tomato (Lycopersicon esculentum Mill. cv. Moneymaker) plants. Heat, causing wounding to a cotyledon, was used to induce both a travelling electrical signal and systemic proteinase inhibitor activity. Intracellular recordings of changes in the membrane potential of different cell types were measured in the petiole of leaf 1, the first true leaf, and impaled cells… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
72
0
3

Year Published

1997
1997
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 136 publications
(78 citation statements)
references
References 32 publications
3
72
0
3
Order By: Relevance
“…15 EPWs are generated by mechanical and physical stimuli [16][17][18] and depend on voltage-activated and possibly mechanosensitive channels along sieve tubes. 14,19 Our recent study 13 showed, that forisomes at 3-4 cm from the stimulus site dispersed 15-45 sec after burning the leaf tip.…”
Section: Modes Of Sieve-plate Occlusionmentioning
confidence: 99%
“…15 EPWs are generated by mechanical and physical stimuli [16][17][18] and depend on voltage-activated and possibly mechanosensitive channels along sieve tubes. 14,19 Our recent study 13 showed, that forisomes at 3-4 cm from the stimulus site dispersed 15-45 sec after burning the leaf tip.…”
Section: Modes Of Sieve-plate Occlusionmentioning
confidence: 99%
“…Cytoplasmic Ca 2ϩ rises sharply during these action potentials (Kikuyama and Tazawa, 1983;Thiel et al, 1997). In higher plants, similar potential waves are transmitted along sieve tubes (Eschrich et al, 1988;Fromm, 1991;Rhodes et al, 1996), where they seem to raise levels of cytoplasmic Ca 2ϩ (Fromm and Spanswick, 1993). It seems a reasonable working hypothesis that exogenously induced turgor changes trigger membrane potential waves in SEs that are accompanied by intracellular Ca 2ϩ surges.…”
Section: Stimuli Triggering Crystalloid Dispersal: Membrane Permeabilmentioning
confidence: 99%
“…A phloem mobile polypeptide called systemin behaves as a systemic signal released from wound sites (Pearce et al, 1991;McGurl et al, 1992McGurl et al, , 1994Narvaez-Vasquez et al, 1995), but severa1 other chemicals, including IAA (Thornburg and Li, 1990), ABA (PeAa-Cortés et al, 1989), and ethylene (ODonnell et al, 1996), have been associated with the signaling pathway and with physical forces such as hydraulic effects (Malone and Alarcon, 1995) and action potentials (Herde et al, 1996;Rhodes et al, 1996;Stankovic and Davies, 1996).…”
Section: Damage To Leaves Of Tomato (Lycopersicon Esculentum)mentioning
confidence: 99%